1992
DOI: 10.1210/endo.130.2.1310281
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone-releasing hormone and neuropeptide Y influence deoxyribonucleic acid replication in three anterior pituitary cell types. Evidence for mediation by growth factors released from gonadotrophs.

Abstract: Treatment of anterior pituitary reaggregate cell cultures from 14-day-old female rats with physiological doses of the gonadotropin-releasing hormone LHRH or neuropeptide Y (NPY) for 40 h dose-dependently increased [3H]thymidine ([3H]T) incorporation into DNA of cells expressing PRL immunoreactivity (PRL-ir) and of those expressing ACTH-ir, whereas these peptides decreased the number of [3H]T-labeled cells expressing GH-ir. The effects of NPY were of the same magnitude as those of LHRH. The effects of LHRH were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 4 publications
1
19
1
Order By: Relevance
“…Gonadotrophs also appear to release paracrine growth factors. This release is stimulated by LHRH as well as by neuropeptide Y (NPY) (Tilemans et al 1992), a peptide which is synthesized within the anterior pituitary (Jones et al 1989) and can influence gonadotroph function (Crowley et al 1987;Shangold & Miller, 1990). These paracrine growth factors from gonadotrophs enhance the number of DNA-replicating lacto¬ trophs and corticotrophs and lower the number of DNA-replicating somatotrophs (Tilemans et al 1992).…”
mentioning
confidence: 99%
“…Gonadotrophs also appear to release paracrine growth factors. This release is stimulated by LHRH as well as by neuropeptide Y (NPY) (Tilemans et al 1992), a peptide which is synthesized within the anterior pituitary (Jones et al 1989) and can influence gonadotroph function (Crowley et al 1987;Shangold & Miller, 1990). These paracrine growth factors from gonadotrophs enhance the number of DNA-replicating lacto¬ trophs and corticotrophs and lower the number of DNA-replicating somatotrophs (Tilemans et al 1992).…”
mentioning
confidence: 99%
“…Very interestingly, the same population of progenitor cells that develops after adrenalectomy also proliferates after gonadectomy (578). We also found enhanced cell mitosis in pituitary aggregate cell cultures during the first week of culture (116) and this mitotic activity was for a large part in nonhormonal cells (393). Other investigators found a three-fold increase in pituitary AVP secretion after a 3-day culture period (570).…”
Section: Corticotrophs As Autocrine/paracrine Cells and Targetsmentioning
confidence: 63%
“…By means of cell separation and recombination experiments, we again showed that the developmental actions of GnRH depend on the presence of gonadotrophs (116). Mediation by paracrine factor(s) was indicated by the finding that medium conditioned by a highly enriched population of gonadotrophs cultured in the presence of GnRH, mimicked the effects of GnRH (120, 121).…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 77%
See 2 more Smart Citations